La prise en compte du magico-religieux dans les problématiques de développement durable : le cas du Ngondo chez les peuples Sawa du Cameroun - Esoh Elamé (VertigO)
This paper attempts to present interaction between culture and development in Sub-Saharan Africa. More concretely, considering traditional religious practices of the Sawa people in Cameroon, we focus upon the necessity to take into consideration the magic religious material and immaterial cultural heritage in the development of the area.